2022
DOI: 10.4102/phcfm.v14i1.3736
|View full text |Cite
|
Sign up to set email alerts
|

Serum prostate specific antigen is a good indicator of prostatic volume in men with benign prostatic hyperplasia

Abstract: Background: Benign prostatic hyperplasia (BPH) is the most common cause of bladder outlet obstruction in men over the age of 50 years. An association between the prostate specific antigen (PSA), International Prostate Symptoms Score (IPSS) and prostate volume (PV) may be instrumental in determining patients who may benefit from treatment. Targeted therapy will reduce the cost of care because it is unwise to treat all men with prostate enlargement to prevent complications when the risk of occurrence is negligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Certain individuals with BPH exhibit abnormal PSA levels, which have been identified as a significant risk factor for the progression of BPH. In the cohort of patients with benign prostatic hyperplasia necessitating surgical intervention, the elevation in PSA levels is notably pronounced ( 5 ). Additional research ( 7 ) has demonstrated that the confluence of benign prostatic hyperplasia and prostatic histological inflammation can exacerbate the deterioration of prostate epithelial cells, leading to an escalation in serum PSA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain individuals with BPH exhibit abnormal PSA levels, which have been identified as a significant risk factor for the progression of BPH. In the cohort of patients with benign prostatic hyperplasia necessitating surgical intervention, the elevation in PSA levels is notably pronounced ( 5 ). Additional research ( 7 ) has demonstrated that the confluence of benign prostatic hyperplasia and prostatic histological inflammation can exacerbate the deterioration of prostate epithelial cells, leading to an escalation in serum PSA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have demonstrated that 78% of individuals with prostatic hyperplasia exhibit inflammatory cell infiltration in postoperative pathology ( 4 ). While prostate-specific antigen (PSA) is a crucial serum marker for diagnosing prostate cancer, numerous studies have highlighted that prostatic hyperplasia can also lead to elevated levels of PSA in the bloodstream ( 5 , 6 ). In addition, as the condition advances, the levels of PSA tend to rise as well.…”
Section: Introductionmentioning
confidence: 99%